Major Adverse Cardiovascular Events in Primary Aldosteronism After Adrenalectomy or Mineralocorticoid Receptor Antagonist Treatment: A Systematic Review and Meta‐Analysis - Chien‐Wei Huang; Tse‐Ying Huang; Ya‐Fei Yang; Li‐Yang Chang; Yu‐Kang Tu; Vin‐Cent Wu; Jui‐Yi Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The object of this study was to investigate the incidence rate of major adverse cardiovascular event (MACE) among patients with primary aldosteronism (PA) after adrenalectomy or mineralocorticoid receptor antagonist (MRA) treatment. Methods and Results A systematic review and meta‐analysis was conducted by searching PubMed, Embase, Cochrane Library, Web of Science, CINAHL, and Scopus through April 15, 2024. Studies reporting the MACE incidence rate in patients with PA after treatment were included. We adapted the random‐effects model and performed subgroup and meta‐regression analyses. A total of 20 studies involving 16 927 patients with PA were included. There were 5939 patients with PA who underwent adrenalectomy. A total of 10 474 patients received MRA treatment. Additionally, 546 patients received either adrenalectomy or MRA treatment. The pooled incidence rate of MACE among patients with PA after treatment was 2.20/100 patient‐years (95% CI, 1.70–2.80), higher than that of non‐PA hypertension (1.20/100 patient‐years [95% CI, 0.70–2.10]). Patients with PA after adrenalectomy had a lower MACE incidence rate (2.00/100 patient‐years [95% CI, 1.40–2.60]) compared with those undergoing MRA treatment (3.30/100 patient‐years [95% CI, 2.40–4.10], P=0.017). Advanced age (coefficient: 0.071, P<0.001) and diabetes (coefficient: 0.070, P=0.001) increased the risk of posttreatment MACE. A curvilinear dose–response relationship between the posttreatment plasma renin activity and the MACE incidence was observed, with the lowest risks at plasma renin activity of 1.0 to 2.0 ng/mL per hour (Pnonlinearity<0.001). Conclusions The MACE incidence in treated patients with PA was 2.20 per 100 patient‐years, higher than in patients with hypertension without PA. Maintaining posttreatment plasma renin activity between 1.0 and 2.0 ng/mL per hour appears crucial for minimizing cardiovascular risk. Adrenalectomy proved more effective than MRA treatment in reducing MACE risk. Advanced age and diabetes significantly increased the risk of posttreatment MACE.